Targeting rubella for elimination - Davendra K Taneja; Pragya Sharma (Wolters Kluwer Medknow Publications, 2012)
Rubella is an acute, usually mild viral disease. However, when rubella infection occurs just before conception or during the first 8-10 weeks of gestation, it causes multiple fetal defects in up to 90% of cases, known as Congenital Rubella Syndrome (CRS). It may result in fetal wastage, stillbirths and sensorineural hearing deficit up to 20 weeks of gestation. Rubella vaccine (RA 27/3) is highly effective and has resulted in elimination of rubella and CRS from the western hemisphere and several European countries. Review of several studies documents the duration of protection over 10-21 years following one dose of RA27/3 vaccination, and persistent seropositivity in over 95% cases. Studies in India show seronegativity to rubella among adolescent girls to vary from 10% to 36%. Although due to early age of infection resulting in protection in the reproductive age group, incidence of rubella in India is not very high. However, due to severity of CRS coupled with introduction of RCV in private sector and in some of the states which is likely to lead to sub-optimal coverage and resulting higher risk of rubella during pregnancy in the coming decades, it is imperative to adopt the goal of rubella elimination. As in order to control measles, the country has adopted strategy of delivering second dose of measles through measles campaigns covering children 9 months to 10 years of age in 14 states, it is recommended to synergize efforts for elimination of rubella with these campaigns by replacing measles vaccine by MR or MMR vaccine. Other states which are to give second dose of measles through routine immunization will also have to adopt campaign mode in order to eliminate rubella from the country over 10-20 years. Subsequently, measles vaccine can be replaced by MR or MMR vaccine in the national schedule.